Faktor Risiko Yang Berhubungan Dengan Kejadian Tuberkulosis Paru Di Wilayah Kerja Puskesmas Kedaton Kota Bandar Lampung - Karbito; Ahmad Fikri; Siti Maisaroh (STIKES Columbia Asia Medan, 2026)
Indonesia ranks second in the world and Bandar Lampung City is the region with the highest TB incidence in Lampung Province with a treatment success rate that is still below the national target. This study aims to analyze the risk factors associated with the incidence of pulmonary TB in the Kedaton Community Health Center Working Area of ​​Bandar Lampung City using a quantitative analytical study with a case-control design. The study sample consisted of 40 cases (smear-positive pulmonary TB patients) and 40 controls (closest neighbors without TB) taken using a consecutive sampling technique, where data were collected through interviews, observations, and measurements using questionnaires and physical measuring instruments at home. The results of the bivariate analysis showed that employment status (p = 0.024) and bedroom ventilation (p = 0.040) had a significant relationship with the incidence of pulmonary TB, while the results of the multivariate analysis using multiple logistic regression showed that gender (p = 0.015) and bedroom ventilation (p = 0.009) were significantly related variables. The conclusion of this study determined that bedroom ventilation was the most dominant variable associated with pulmonary TB incidence, with inadequate ventilation having a 3.91-fold increased risk (OR=3.91; 95%CI=1.41-10.94) compared to adequate ventilation after controlling for gender.